Impact of Foreign Exchange Administration Rule on the Nexus between Country-Specific FDI and Malaysian Currency - Wee-Yeap Lau; Tien-Ming Yip (Australasian Accounting, Business and Finance Journal, 2021)
In the aftermath of the US Presidential election on 8 November 2016, the Malaysian currency Ringgit (MYR) had witnessed unprecedented volatility in its value relative to the USD. As a policy response, Bank Negara Malaysia (BNM) implemented a Supplemental Foreign Exchange Administration (SFEA) Rule in December 2016. Exporters are required to convert 75 per cent of foreign currency proceeds from the exports of goods into MYR with a licensed onshore bank. This study evaluates the impact of the new SFEA Rule on the relationship between country-specific FDI and MYR. Based on the data of five major inward FDI countries from 2015 to 2018, our results show: Firstly, Japanese FDI strengthens MYR in post-SFEA Rule; Secondly, FDI from Singapore is found to exert downward pressure on MYR; Thirdly, FDI from China, the Netherlands and the US are insignificant in influencing the MYR; Finally, inward FDI from different countries responds differently to the Rule. Notably, the results obtained are robust to different measures of the exchange rate. On policy suggestion, the Foreign Exchange Rule should also target non-export oriented inward FDIs to achieve the policy target. The result also highlights the importance of export-oriented FDIs for the long-run benefit of the Malaysian economy.
Keywords: foreign exchange rule; exchange control; Malaysia; Japanese investment; foreign direct investment